Florida 4-H Horticulture Identification and Judging: Contest Rules and Glossary - Jeffrey G. Williamson; Sydney Park Brown; Tom Wichman (EDIS)
Revised! 4H-PSJ-20, a 16-page illustrated fact sheet by Jeffrey G. Williamson, Sydney Park Brown, and Tom Wichman, provides guidelines and information for Florida 4H members and Master Gardeners interested in horticulture and/or in participating in state contests held annually at 4-H Congress or the Master Gardener Annual Conference. This publication combines and supersedes 4H-PSJ-20 (Rules and Glossary), 4H-PSJ-21 (Flowers and Foliage Plants), 4H-PSJ-22 (Fruits and Nuts), 4H-PSJ-23 (Ornamentals), 4H-PSJ-24 (Vegetables), and 4H-PSJ-25 (Score Sheet). Published by the UF Department of Environmental Horticulture, August 2009.